KEMAMPUAN GURU DALAM MENGELOLA KELAS DI MIN SIBUHUAN - Faridah Sa’diyah Hasibuan (CV. ADIBA AISHA AMIRA, 2024)
Seeing how important it is to manage this class, the author is interested in exploring further how teachers can develop more dynamic classes to achieve the expected goals. For that, the author tries to research: